EFEKTIVITAS TERAPI HUMOR DENGAN MEDIA FILM KOMEDI UNTUK MENURUNKAN TINGKAT KECEMASAN PADA LANSIA - Ni Luh Deliyani; Marlina S; Mahajudin Mahajudin; Sri Adiningsih adiningsih (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2019)
The aging process was a natural process in human that the changing occured or function decline of biological, psychological, social, cultural and spiritual. One of the mental health problems that often arised in the elderly was anxiety. The managing of anxiety in the elderly could be done by humor therapy. Humor, basically contained a charge of positive emotions, allowing people to think more broadly, flexibly and creatively to solve the problems. Comedy as one of the stimulus could cause a sense of humor. This study aimed to determine the effectiveness of humor therapy by watching comedy movie on the decreasing of anxiety level in the elderly. This quasi-experimental study was conducted at Panti Tresna Werdha Hargo Dedali Surabaya, by using non-randomized control group pretest posttest design. Samples that met the inclusion criteria were 18 that were divided to two groups based on the block. Ten persons in the east block were treated by watching comedy movie and eight in western block were used as control group. Both groups performed pretest and posttest at the same time to determine the level of anxiety, using the Hamilton Rating Scale for Anxiety (HRS-A). Wilcoxon Signed Ranks Test results z= -2.460 and p= 0.014 that there was different of anxiety level before and after humor therapy in the treated group. The control group results, z= -1.000 and p= 0.317 show there was no different in anxiety levels. Wilcoxon Mann Whitney Test results z= -2.379 and p= 0.017 that there was different in anxiety level between the treated group and control group. Effectiveness of humor therapy by watching comedy movie to decrease anxiety level was 34.7%. The conclusion of the study suggests humor therapy by watching comedy movie can decrease the anxiety level in the elderly at Panti Tresna Werdha Hargo Dedali Surabaya.